Patentar la vida: un poco de metafísica y otro poco de empiria - Bertomeu, María Julia (2011)
Patents are temporary monopolies conceded by political authorities to private agents on the grounds that they support the public interest. Since Locke, there has been a lot of philosophical and legal discussion on the conditions under which the fiduciary privatization of "commons", i.e., public resources held in common, should proceed. An important legal, philosophical and economic debate has recently begun on the privatization of life forms through patents. Alter restating the fiduciary conception of private appropriation based on Lockean grounds and on the tradition of our modern positive legal framework, this paper explores some of the metaphysical, legal, political and economic issues involved in the current discussion.